Application of OECI Accreditation Program to Cancer Institutes of the Alleanza Contro il Cancro Italian Network: A Special Project Supported by the Italian Ministry of Health. (December 2015) - Paradiso, Angelo; Belardelli, Filippo
The Ministry of Health of the Italian government requires for Italian Comprehensive Cancer Centers, called Istituti di Ricovero e Cura a Carattere Scientifico (IRCCS), to be certified according to international models. In this perspective, considering of particular interest the recent model for accreditation of cancer centers developed by the Organisation of European Cancer Institutes (OECI), the network of Italian IRCCS participating in Alleanza Contro il Cancro activated a project, supported in 2010 by the Ministry of Health, with the primary objective to verify the applicability of the OECI model to the Italian network of IRCCS. All 11 cancer IRCCS took part in the project. We describe in detail the activities performed, the results reached, and the impact of the initiative on the National Health Service. The initiative was concluded in November 2015 with the certification of all the Italian cancer IRCCS. Italy is the only European country that has applied the modern and tailored accreditation model of OECI to all their cancer centers.